The relationship between déjà vu and ru’yā ṣādiqah in the qur’an: athematic exegetical analysis - Marsella; Endang Saeful Anwar; Hikmatul Luthfi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study examines the relationship between déjà vu in modern psychology and ru’yā ṣādiqah in the Qur’an as forms of anticipatory inner experience that appear to precede real events. The research aims to identify points of convergence at the level of human experience while critically distinguishing their epistemological foundations. A qualitative interdisciplinary design was employed, combining thematic Qur’anic exegesis with conceptual analysis of contemporary psychological theories. Relevant Qur’anic verses concerning ru’yā were systematically collected and interpreted using a thematic approach, then analytically compared with psychological explanations of déjà vu, particularly those related to memory processing, perceptual familiarity, and dream-based cognition. The findings reveal that both phenomena produce a strong sense that an event has been previously experienced before its actual occurrence, indicating a shared phenomenological structure. However, this similarity does not extend to their underlying nature. Déjà vu is identified as a cognitive phenomenon arising from internal processes such as memory mismatch and subconscious activation, resulting in uncertain and non-verifiable impressions. In contrast, ru’yā ṣādiqah is presented in the Qur’an as a structured and meaningful experience rooted in divine communication, characterized by clarity, truth, and eventual realization in historical reality. Their temporal structures also differ, with déjà vu reflecting retrospective recognition, whereas ru’yā ṣādiqah embodies prospective anticipation that is later confirmed. This study contributes by proposing a framework of phenomenological correspondence with epistemological divergence, offering a rigorous interdisciplinary perspective that maintains the distinction between cognitive experience and revelation.